“Sisikapin, Aabutin”: Hassles and Drives of Working Students in a State University - Regine Natali D. Farrales; Mark F. Antonio; Emmalyn Kaye P. Cabalar; Sandara A. Mendoza; Eric DS. Ebro (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
While previous research highlights the general struggle of working students, a specific gap exists in understanding how institutional support can effectively mitigate role strain within the Philippine state university system. This explored the lived experiences of working students at President Ramon Magsaysay State University, San Marcelino Campus, San Marcelino Zambales. Using a phenomenological qualitative design, it identified both “hassles” (challenges) and “drives” (inspirations). Data were gathered from tem participants through in-depth interviews using an instruments validated by one faculty experts in educational management. Findings revealed that despite facing Time Management and Role Conflicts, students developed a greater sense of resilience and purpose. This study identifies ways the university can provide targeted support to meet students’ diverse needs and foster their persistence.